Effect of folate status and methylenetetrahydrofolate reductase genotypes on the complications and outcome of high dose methotrexate chemotherapy in north Indian children with acute lymphoblastic leukemia - Moulik, Nirmalya Roy (Indian J Med Paediatr Oncol, 2016)
PURPOSE: The genes of the folate metabolic pathway have been associated with toxicities during high dose methotrexate therapy for childhood ALL, however, the importance of intrinsic folate status in this regard is unclear. METHODS: In the present study the effect of precourse folate levels and MTHFR genotypes on the complications during high dose methotrexate chemotherapy in children with ALL were examined. RESULTS: Twenty-one children were studied. Folate deficiency was associated with higher incidence of neutropenia (P = 0.03) and longer duration of chemotherapy interruption (P = 0.009). Children with MTHFR1298 mutations needed more red cell transfusion (P = 0.03). All 3 deaths encountered were seen in folate deficient children. CONCLUSIONS: Folate deficiency was associated with higher complications during high dose methotrexate therapy, the implications of which are important especially in resource poor settings with high prevalence of folate deficiency.